Pengaruh Penggunaan Gadget dan Perilaku Sosial Terhadap Prestasi Belajar Peserta Didik di Sekolah Dasar - Risnawati Risnawati; Darman Manda; Suardi Suardi (Phinisi Integration Review, 2022)
The purpose of this study was to determine: (i) The effect of using gadgets on student learning achievement in Cluster I Region 3 Barru District, Barru Regency, (ii) The effect of social behavior on student learning achievement in Cluster I Region 3 Barru District, Barru Regency. (iii) The effect of using gadgets and social behavior on the learning achievement of students in Cluster I Region 3, Barru District, Barru Regency. The research method used is a survey research type with a quantitative approach. The data collection techniques used are questionnaires and documentation. The population in this study is cluster I, region 3, sub-district, Barru, Barru Regency, with a total of 168 students and a sample of 119 students using the Krejcie table. The results of this study indicate (i) There is an effect of using gadgets on learning achievement in Cluster I region 3, Barru sub-district, Barru Regency, (ii) There is an influence of social behavior on learning achievement in Cluster I region 3, Barru sub-district, Barru Regency. (iii) There is an effect of gadget use and social behavior on learning achievement in cluster I Region 3 Barru District, Barru Regency